Recommendations for medical care in the pediatric oncology camp setting: Consensus statements based on Delphi methodology. Issue 3 (3rd December 2019) - Alexander, Sarah; Science, Michelle; Breakey, Vicky; Clarke, Averill; Gibson, Paul
Abstract: For many children with cancer, participation in oncology camp programs is an important component of healing that offers opportunities for fun and can have substantial impacts on social and physical well‐being. Optimal medical care and infectious screening for children attending oncology camp is critical to maximize safety and opportunities for participation. This paper describes recommendations for a series of common medical issues unique to the care of children with cancer in the camp setting generated by a modified Delphi consensus approach.